Fire Is Associated With Positive Shifts in Bumble Bee (Bombus vosnesenskii) Body Size and Bee Abundance in the Southern Sierra Nevada Mountains - Claudinéia P. Costa; Natalie Fischer; Melissa Arellano; Claudette C. Torres; S. Hollis Woodard (Ecology and Evolution)
ABSTRACT Climate change is increasing the frequency and severity of wildfires worldwide. Although wildfires are typically viewed as destructive, emerging research suggests they may have benefits for some species, including some pollinators. One reason for this is that wildfires can increase floral resource availability in the years immediately following the burn, potentially creating more favorable conditions for pollinator foraging and reproduction. In this study, we focused on how the 2021 KNP Complex Fire impacted the bumble bee Bombus vosnesenskii in the Southern Sierra Mountains, where the effects of fire on this pollinator species have not been previously explored. Consistent with bumble bee studies in other areas, we found an increase in the size of B. vosnesenskii workers in recently burned areas. This effect was detectable despite a limited number of sampling events and locations in our study, and irrespective of the habitat type (meadow vs. forest) in which sampling occurred. We failed to detect increased floral resource availability (abundance or diversity) in burned areas but did observe unique floral communities in burned areas. Our findings contribute to our growing understanding of fire's impact on pollinators and support the broad idea that fire might have benefits for some organisms.